The Effect of Work Facilities on Employee Performance in the Office of Investment and One-Stop Services, Gowa Regency, South Sulawesi, Indonesia. - Nasrullah, Muh; Sumarto, Sitti Sarah; Baharuddin, Aris; Zainal, Henni; A. Caezar to Tadampali (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This study aims to determine the use of work facilities on the performance of employees at the Office of Investment and One-Stop Services, Gowa Regency. The data collection techniques used were questionnaires and documentation with a population of 36 people. While the data analysis technique used is a descriptive statistical analysis using percentages and for inferential statistical analysis techniques using data normality test, product-moment correlation analysis, and simple linear regression analysis. The results showed that the working facilities at the Investment and One-Stop Integrated Services Office of Gowa Regency were in a very good category. The performance of employees at the Office of Investment and One-Stop Services of Gowa Regency is in the very good category which is seen from 1) quantity (90%) 2) quality (88%) 3) timeliness (89%) 4) attendance (89%) ), and 5) ability to work together (82%). Based on the product-moment correlation test analysis, it is stated that there is a positive and significant effect of the use of work facilities on the performance of employees at the Office of Investment and One-Stop Services, Gowa Regency by 52%, stated that it is accepted with a strong level of influence. From the results of simple linear regression analysis, it shows that there is an influence of the Office of Investment and One-Stop Services of Gowa Regency.